2022
DOI: 10.1128/spectrum.02358-22
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Effectively Rescues Pneumonia Caused by Prevalent Multidrug-Resistant Klebsiella pneumoniae in the Early Stage

Abstract: K. pneumoniae is recognized as the most common pathogen of hospital- and community-acquired pneumonia across the world. The strains of ST11 and ST383 are frequently reported in patients with pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…On the 7th-day post-challenge, TNF-α levels in the phage-treated infected groups were significantly lower than in the un-treat group but still high than in the synergism group. The involvement of the immune response in the success of respiratory phage therapy was previously demonstrated and modeled [ 55 ]. Another study showed phages targeting host strains regulate pro-inflammatory and anti-inflammatory cytokines in mice [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the 7th-day post-challenge, TNF-α levels in the phage-treated infected groups were significantly lower than in the un-treat group but still high than in the synergism group. The involvement of the immune response in the success of respiratory phage therapy was previously demonstrated and modeled [ 55 ]. Another study showed phages targeting host strains regulate pro-inflammatory and anti-inflammatory cytokines in mice [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The minimum lethal dose (MLD)was determined, and the animal model was constructed according to previous reports [ 21 , 22 ]. Briefly, the mice were randomly allocated into four groups: (1) the K. aerogenes group (n = 25), which received an intratracheal/endobronchial instillation of 2 × 10 7 CFU K. aerogenes (2 × MLD) and intranasal delivery of normal saline; (2) the K. aerogenes + pK4-26 group (n = 25), which received an intratracheal/endobronchial instillation of 2 × 10 7 CFU K. aerogenes and intranasal delivery of 2 × 10 9 PFU pK4-26; (3) the pK4-26 group (n = 25), which received an intratracheal/endobronchial instillation of normal saline and intranasal delivery of 2 × 10 9 PFU pK4-26; and (4) the paired group (n = 25), which received an intratracheal/endobronchial instillation of normal saline and intranasal delivery of normal saline.…”
Section: Methodsmentioning
confidence: 99%
“…In a mouse model of infection, phage treatment improved survival; 53 it was demonstrated that phage pKp11 and pKp383 lysed 51 strains of multidrug-resistant K. pneumoniae (including strains ST11 and ST383), providing an effective treatment for the early stages of pneumonia in a mouse model of infection without significant side effects. 54 Scientists at the National Institutes of Health (NIH) successfully treated mice infected with multidrug-resistant K. pneumoniae ST258 using two different phage viruses, alone and in combination. These findings are encouraging and show successful therapeutic effects in animal models.…”
Section: Phagesmentioning
confidence: 99%